2019
DOI: 10.3390/molecules24132411
|View full text |Cite
|
Sign up to set email alerts
|

NFBTA: A Potent Cytotoxic Agent against Glioblastoma

Abstract: Piplartine (PPL), also known as piperlongumine, is a biologically active alkaloid extracted from the Piper genus which has been found to have highly effective anticancer activity against several tumor cell lines. This study investigates in detail the antitumoral potential of a PPL analogue; (E)-N-(4-fluorobenzyl)-3-(3,4,5-trimethoxyphenyl) acrylamide (NFBTA). The anticancer potential of NFBTA on the glioblastoma multiforme (GBM) cell line (U87MG) was determined by 3-(4,5-dimethyl-2-thia-zolyl)-2, 5-diphenyl-2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 91 publications
0
27
0
Order By: Relevance
“…In consequence, the docking predicted complexes are not necessarily stable. Previous studies have shown that many predicted ligandreceptor complexes, although presenting favorable interactions might not be feasible [44,45]. To further refine the possible mechanism of action of compound 7, MD simulations and MM-PBSA calculations were performed as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, the docking predicted complexes are not necessarily stable. Previous studies have shown that many predicted ligandreceptor complexes, although presenting favorable interactions might not be feasible [44,45]. To further refine the possible mechanism of action of compound 7, MD simulations and MM-PBSA calculations were performed as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…The OMEGA software [41] was used to obtain the initial 3D structure of compound 7, and AM1-BCC charges were added to it with MOLCHARGE [42]. Molecular docking of compound 7 to its potential targets was performed with Gold [43] following the same procedure as in our previous research [44,45]. Water molecules, cocrystalized ligands, and cofactors not involved in ligand binding were removed from the receptors.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Overall, the docking results did not allow for confident selection of the most probable compound 9 targets. Post-processing of predicted docking complexes using Molecular Dynamics (MD) simulations along with estimations of free energies of binding can help refine target prioritization [ 44 , 65 ]. Calculations were thus performed (described in the Methods section) to estimate the free energies of binding for compound 9 to its predicted targets using the MD simulations data.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking followed the same protocol described in our previous publications [ 44 , 65 ]. The initial three-dimensional conformation of compound 9 was obtained with OpenEye Omega [ 79 ]; and AM1-BCC partial atomic charges were added to it using Molcharge [ 80 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selection of the most probable binding modes of each compound to M pro was carried out following the previously described consensus scoring methodology [55,57,58]. Consensus scoring took place independently for each compound to rank its 30 predicted binding modes.…”
Section: Molecular Dockingmentioning
confidence: 99%